Genetic and morphological diversity of the genus Lampetra (Petromyzontidae) in Europe - Mateus, Catarina Sofia Pereira (2013)
This study aims at contributing to the knowledge on genetic and morphological diversity of European Lampetra. Mitochondrial DNA was used to infer the phylogeography of this genus, and further define conservation units in the Iberian Peninsula. Morphological data was then combined to describe three new species endemic to Portugal. These results support evidence of the high diversity of the Iberian Peninsula, a region that acted as glacial refugium during the Pleistocene glaciations. The analysis of microsatellite loci allowed to understand the postglacial colonization processes and to assess contemporary gene flow between Lampetra species in Europe. The use of genome-wide sequencing significantly contributed for a better knowledge about the taxonomic validity of lamprey paired species, identifying strong divergence between species. The information gathered with this study greatly contributes to the knowledge on lampreys, a group of particular interest in evolutionary studies that constitutes a great model system to study speciation processes; ### Resumo: Diversidade genética e morfológica do género Lampetra (Petromyzontidae) na Europa Este estudo pretende contribuir para o conhecimento da diversidade genética e morfológica do género Lampetra na Europa. A filogeografia deste género, e posterior definição de unidades de conservação na Península Ibérica, foi inferida através de ADN mitocondrial. A junção de dados morfológicos permitiu a descrição de três espécies novas, endémicas de Portugal. Estes resultados suportam as evidências acerca da elevada diversidade da Península Ibérica, uma região que atuou como refúgio glaciar durante o Plistocénico. A análise de microssatélites permitiu estudar os processos de colonização pós-glaciais e detetar fluxo genético recente entre espécies de Lampetra na Europa. O uso de genómica contribuiu significativamente para um melhor conhecimento da validade taxonómica de espécies pares, identificando forte divergência entre espécies. A informação recolhida no âmbito desta tese contribuiu significativamente para o conhecimento das lampreias, um grupo de particular interesse em estudos evolutivos que constitui um excelente modelo para estudar os processos de especiação.